Atomically dispersed Au catalysts supported on CeO2 foam: controllable synthesis and CO oxidation reaction mechanism. Issue 43 (26th October 2017) - Wang, Hao; Shen, Jianhua; Huang, Jianfei; Xu, Tengjing; Zhu, Jingrun; Zhu, Yihua; Li, Chunzhong
Abstract : The Au atoms on CeO2 foam are a more stable site for CO adsorption on the catalysts. Abstract : CO oxidation is a typical heterogeneous catalytic reaction. Development of active and stable low-temperature CO oxidation catalysts has been one of the hot topics in the field of catalysis. In this work, we explored the catalytic application of a series of Au catalysts supported on CeO2 foam using a modified deposition–precipitation method for CO oxidation. Among them, the catalyst with 1.1% Au loading content showed the highest catalytic activity, leading to the CO total conversion at 20 °C. Based on the strategy of stepwise reduction of Au loading content, we finally obtained the atomically monodisperse Au/CeO2 catalyst with high stability and strong resistance to elevated temperature, on which in situ DRIFTS analysis and DFT study were further performed to study the possible reactive site. Our results implied that the Au atoms on the CeO2 foam are the more stable sites for CO adsorption on the catalysts.